The incidence of nontransfusion-transmitted infectious diseases in β thalassemia major patients at Cipto Mangunkusumo Hospital - Zakiudin Munasir; Amy Diana Ruth; Alan Roland Tumbelaka (Paediatrica Indonesiana, 2003)
Background The statement that thalassemic children are moreprone to infection than normal children has been accepted as apart of thalassemia literatures for years. Recently this concept hasbeen questioned, and certainly it has impressed the clinicians thatthe incidence of infection in thalassemia in early childhood is re-duced by adequate blood transfusion although this has not beendocumented. However, iron overload favors bacteria to acquireiron necessary for their growth. Excess iron deposit may damageimmune response in thalassemic patients.Objective The aim of this study was to find out whether there wasany increasing episode of nontransfusion-transmitted infectious dis-eases in thalassemic patients.Design Observational, cross sectional study.Setting Thalassemia outpatient clinic at the Department of ChildHealth, Cipto Mangunkusumo Hospital, Jakarta, Indonesia.Patient Two hundreds subjects by consecutive sampling, groupedby their total volume of transfusion into ≥5 liters or <5 liters groups.Results The numbers of patients receiving transfusion ≥5 literswho had 1,2,3,4 and 5 times episodes of influenza in 6-month pe-riod were 69, 20, 3, 2, and 2 out of 173 patients respectively andin patients receiving transfusion less than 5 liters,14/27 had influ-enza for 1-2 times in 6-month period. The incidence of diarrhea inpatients receiving transfusion ≥5 liters was 11.5%, once to twice in6 months and in patients receiving transfusion less than 5 liters, 7/27, 1-2 times in 6 months. There was no difference in the inci-dence of influenza and diarrhea between the two groups.Conclusion It seemed that there was no any increasing incidenceof nontransfusion-transmitted infectious diseases in thalassemicpatients in accordance with total volume of blood transfusions